Économie palestinienne : de quoi parle-t-on (encore) ? - Taher Labadi (Revue des Mondes Musulmans et de la Méditerranée)
What do we speak of when we speak of the “Palestinian economy”? This question echoes both today’s stalemate in the Palestinian national project and the “failure of the two-state solution”. To answer, this paper operates a double break, the first being a separate analysis of the Palestinian and Israeli economies (dual approach), the second, being the usual distinction that prevails in economists' discussions of economics and politics. To this end, we examine three proposals: (a) Palestinian economic initiative is caught in a colonial style confrontation with Israel; (b) International aid to Palestinians aggravates their dependency and subjugation; (c) Palestinian economic activity is dominated by a globalized rent seeking elite.